Depression and anxiety in palliative care inpatients compared with those receiving palliative careat home - Austin, P.; Wiley, S.; McEvoy, Peter; Archer, L. (Cambridge University Press, 2011)
Objective: This study compared the prevalence of anxiety and depression as measured on the Hospital Anxiety and Depression Scale (HADS) in palliative care patients being treated at home with those being treated as inpatients.Method: The participants were palliative care patients being treated at home (n ¼ 46) and palliative care inpatients (n ¼ 46). Subjects were assessed for functionality on the Karnofsky Performance Status Scale (KPS) and anxiety and depression were measured on the HADS.Results: The results showed that 20% of all patients were depressed and anxious as measured on the HADS, regardless of the cutoff criteria. There was no significant difference in depression and anxiety between the two groups when socioeconomic status and functionality were controlled for. Functionality, as measured on the KPS, was uniquely a predictor of depression, and younger patients were shown to have greater anxiety. Significance of results: The results suggest that home-based palliative care patients and palliative care inpatients should receive equal psychological support, and that clinicians need to be aware of the psychological vulnerability of younger and less-functional patients. The prevalence of depression and anxiety indicates that all palliative care patients should be screened for psychological distress, to identify those who need further assessment and treatment.